Can telephone data contribute to a national influenza surveillance system in Australia? A retrospective analysis - Mica Hartley; Janice Biggs; Kathryn Glass (University of New South Wales, 2024)
Introduction:   Data collected from telephone helplines that provide health advice can improve the timeliness and accuracy of disease surveillance, contributing to an appropriate and rapid public health response.  We show how these data can forewarn health professionals of increased rates of influenza-like illness (ILI) in the community and discuss implications for COVID-19 syndromic surveillance.   Methods:   The healthdirect helpline (HH) captures demographic details and characteristics of symptoms from users in 6 Australian states and territories.  We compare ILI activity in the HH with ILI activity in emergency department (ED), laboratory, Flutracking and general practice (GP) data using cross-correlation functions.    Results:   Helpline data correlated strongly with ED data (range in yearly correlations from 0.82-0.99), GP data (0.66 - 0.95) and Flutracking data (0.62-0.89), but yearly correlations with laboratory data varied (0.49-0.95).  The highest correlation with laboratory and GP data occurred when HH activity was 1-2 weeks in advance of these data, while correlations with ED and Flutracking data were strongest with no time lag.   Discussion:   Our analysis demonstrates that the number of ILI-related calls to the HH is a reliable indicator of ILI incidence in Australia.  An increase in calls is likely to occur simultaneously with an increase in visits to EDs and prior to an increase in positive laboratory influenza tests and visits to GPs.  A surveillance system including these data would assist health practitioners to receive timely and accurate estimates of the level of ILI in the community to better respond to and prepare for seasonal and epidemic influenza.